The Portfolio – a More Responsible Student – a Less Stressed-out Teacher - Soča Fidler (ELOPE, 2005)
The article warns against the negative impacts of external assessment. These impacts are already noticeable in Slovenia, specifically and mainly in the teaching approach and learning efforts used for taking the standardised Matura exams. There is a narrowing of overall learning goals and a neglecting of the areas that, although vital for students’ development, are not assessed in the exams themselves, as well, there are increased stress levels before and during the exams, which could result in a poorer performance. The article then proposes a portfolio approach in which students set their own learning goals, pursue them, reflect both on their achievements and alternative ways to make better progress. The portfolio approach lends itself extremely well to developing a student’s writing skills gradually, as the awareness of learning goals and the setting of one’s own, in combination with self-assessment and reflection are better motivators than just following preset objectives.